The Comparison of Styloid Processes in the Edentulous and the Posterior Dentate Patients Using Panoramic Radiography - Numan Dedeoğlu; Gözde Eşer; Oğuzhan Altun (Mashhad University of Medical Sciences, 2021)
Introduction: The aim of this study was to evaluate the length of styloid processes of edentulous and posterior dentate patients retrospectively using digital panoramic radiography. Methods: This study was carried out in southwestern of eastern Anatolia region Turkish population. In this study, 100 styloid processes of each of edentulous and posterior dentate patients were measured on digital panoramic radiographs. Styloid process longer than 30 mm was evaluated as an elongated styloid process. Recording of data was performed based on gender, side and groups, Chi-square and Mann Whitney U test were conducted for statistical analysis. Results: Styloid process length was not found to be statistically significant between edentulous (24.9±6.66) and posterior dentate (25.75±5.64) groups (p˃0.05). The frequencies of Elongated styloid processes were not statistically different between genders, side or groups (p˃0.05). Conclusion: Being edentulous was not an important factor for the length of the styloid process and the likelihood of symptoms that might develop.